Who are the patients with extrapulmonary tuberculosis? - Sanches, I (2015)
Introduction: Tuberculosis (TB) remains a major global public health problem and 20% of all cases are extrapulmonar. The purpose of this study was to identify risk factors associated with extrapulmonar tuberculosis. Methods: We carried out a transversal study which included all patients with extrapulmonary tuberculosis registered in a TB reference center in northern Portugal, between January 2008 and January 2012. We evaluated demographic data, comorbidities, BCG vaccination and previous tuberculosis treatments. Multivariable logistic regression was used to identify independent risk factors (p < 0.05). Results: Among the 386 patients studied, 260 (67.4%) had pulmonary tuberculosis (PTB) and 126 (32.6%) extrapulmonary TB (EPTB). Age over 40 years old (OR = 2.09; 95%CI: 1.29–3.38), female gender (OR = 1.63; 95%CI = 1.02–2.6) and HIV infection (OR = 2.72, 95%CI = 1.25–5.93) were independent risk factors for EPTB. Alcoholism (OR = 2.22, 95%CI: 1.00–4.95) was associated with higher risk for PTB. Previous liver disease (OR = 22.30; 95%IC: 1.89–263.57) was an independent risk factor for peritoneal TB. HIV co-infection (OR = 12.97; 95%IC: 1.71–48.42) and the presence of previous TB treatment (OR = 7.62; 95%IC: 1.00–57.9) increase the risk of disseminated disease. Conclusion: We identified independent risk factors for EPTB. Recognizing risk factors associated with EPTB is essential for suspicion of disease and may help make an accurate diagnosis.